(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: An understanding of epidemiological trend in hospital admissions, including diseases and death pattern, is critical for health care planning, appropriate resource allocation & improving existing services facilities. To evaluate the disease and death pattern of children admitted in the Department of Child Health, Bangubandhu Memorial Hospital. Chattogram. Materials and methods: This was a retrospective study. The case records of all patients admitted in the Department of Child Health from Jan 1, 2015 to Dec 31, 2016 were analyzed. Results: Total 3560 children were admitted during this study period. All the patients were distributed into three age groups. Infant, under five and more than five age groups constitute 35%, 33% and 32% respectively. Acute watery diarrhea (33%) bronchiolitis (21%) Bronchopneumonia (10.5%) hereditary hemolytic anemia (9%) and Enteric fever (4.3%) were the five top disease in two years of admission. Among them total 12 (0.34%) patient died. Highest case fatality rate was found in bronchopneumonia (75%). Other common causes of death include meningitis (17%) and heart failure (8.5%). Patient came from urban area was 63% and 37% came from rural area. Conclusion: Admission related findings of this study will help to evaluate the disease pattern of a hospital and planning for more effective case-management strategies. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 31-35